1999
DOI: 10.1007/bf03168774
|View full text |Cite
|
Sign up to set email alerts
|

Web-based viewing of picture archiving and communications systems images—Part II: The effect of compression on speed of transmission

Abstract: Now that picture archiving and communications systems (PACS) has matured, our challenge is to make the images available to the referring physician and, in a teaching institution, to make these images available for conferences and rounding. One solution is the distribution of the images using web-based technology. We investigated a web-based add-on to our PACS to determine the characteristics of the personal computer that will make this technology useful and affordable. We found that images can be viewed easily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Especially in the case of MR images we found evidence in different series that with processor speeds above 500 MHz and a quick 100-Mbit/s network the TTD was prolonged using lossy compression. Interestingly, Bennett et al [19] reported the same behaviour for cross-sectional images, although in their study the TTD with lossy compression increased beginning with a PC with 300 MHz. They explained this mainly through the necessary decompression time on the PC.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Especially in the case of MR images we found evidence in different series that with processor speeds above 500 MHz and a quick 100-Mbit/s network the TTD was prolonged using lossy compression. Interestingly, Bennett et al [19] reported the same behaviour for cross-sectional images, although in their study the TTD with lossy compression increased beginning with a PC with 300 MHz. They explained this mainly through the necessary decompression time on the PC.…”
Section: Discussionmentioning
confidence: 59%
“…It is noteworthy that the network employed was fully switched and with a gigabyte backbone, both features allowing a high data throughput. With a slower network the TTD generally increases because this becomes a bottleneck, which is likely to be one of the reasons, together with the server performance, for the overall longer TTD values obtained by Bennett et al [14,19].…”
Section: Discussionmentioning
confidence: 91%
“…Existem muitos artigos na literatura especializada apresentando soluções e estratégias para a implantação de redes PACS em hospitais e serviços de saúde , e outros discutindo os componentes e interfaces dos sistemas (16)(17)(18)(19)(20)(21)(22) . Esses artigos apresentam, no geral, soluções baseadas em componentes comerciais em conjunto com componentes desenvolvidos, ou customizados, por equipes locais, sendo implantadas modularmente de modo a tentar minimizar impactos e gastos, possibilitando a aquisição de conhecimentos que deverão ser utilizados no planejamento e implementação das etapas posteriores.…”
Section: Armazenamento De Imagensunclassified
“…A sufficient amount of information exists for the client performance and requirements [5,6,7], but the available material on the important server component is dedicated to the download properties [8]. However, a realistic assessment requires a thorough analysis of the upload as well as the download behaviour and especially the interdependency between those two processes.…”
Section: Introductionmentioning
confidence: 99%